TCD (Table Connector Design) / Ramlan Mustapha ... [et al.] - Mustapha, Ramlan; Mahmud, Maziah; Mat Hassan, Surita Hartini; Malkan, Siti Norma Aisyah; Che Hassan, Nurul Hidayah (2021)
Academic writing is essential for students to complete their studies successfully and to compete professionally. University students are required to write based on various styles and are evaluated for their ability to write proficiently. This Table Connector Design (TCD) software is developed to improve writing skills, organise facts and organise academic writing data more systematically. It was developed to offer a fast, easy and user-friendly approach to academic writing that organises facts as found in the literature. The software also helps arrange ideas and facts in the form of a table that can be arranged and rearranged quickly and accurately to suit changing contexts and purposes.